Patellar Tendinopathy. (September 2015) - Schwartz, Aaron; Watson, Jonathan N.; Hutchinson, Mark R.
Context: Patellar tendinopathy is a common condition. There are a wide variety of treatment options available, the majority of which are nonoperative. No consensus exists on the optimal method of treatment. Evidence Acquisition: PubMed spanning 1962-2014. Study Design: Clinical review. Level of Evidence: Level 4. Results: The majority of cases resolve with nonoperative therapy: rest, physical therapy with eccentric exercises, cryotherapy, anti-inflammatories, corticosteroid injections, extracorporeal shockwave therapy, glyceryl trinitrate, platelet-rich plasma injections, and ultrasound-guided sclerosis. Refractory cases may require either open or arthroscopic debridement of the patellar tendon. Corticosteroid injections provide short-term pain relief but increase risk of tendon rupture. Anti-inflammatories and injectable agents have shown mixed results. Surgical treatment is effective in many refractory cases unresponsive to nonoperative modalities. Conclusion: Physical therapy with an eccentric exercise program is the mainstay of treatment for patellar tendinopathy. Platelet-rich plasma has demonstrated mixed results; evidence-based recommendations on its efficacy cannot be made. In the event that nonoperative treatment fails, surgical intervention has produced good to excellent outcomes in the majority of patients.